Hello, my name is awesome : how to create brand names that stick - Watkins, Alexandra (BK business book., 2014)
"Naming a business or product has always been challenging--and sometimes costly--for entrepreneurs and inventors, but it's one of the most important decisions they have to make. Alexandra Watkins presents a foolproof model that anyone can use to create and evaluate brand names like a pro"--